k -mean alignment for curve clustering - Sangalli, Laura M.; Secchi, Piercesare; Vantini, Simone; Vitelli, Valeria (Computational statistics & data analysis, 2010)
The problem of curve clustering when curves are misaligned is considered. A novel algorithm is described, which jointly clusters and aligns curves. The proposed procedure efficiently decouples amplitude and phase variability; in particular, it is able to detect amplitude clusters while simultaneously disclosing clustering structures in the phase, pointing out features that can neither be captured by simple curve clustering nor by simple curve alignment. The procedure is illustrated via simulation studies and applications to real data.